Faktor-Faktor yang Memengaruhi Kemiskinan di Sulawesi Selatan dalam Kerangka Ekonomi Biru Tahun 2023 - Muhtar, Azwar; Setiadi, Yaya (Seminar Nasional Official Statistics, 2025)
The concept of the blue economy emphasizes the sustainable use of marine resources to support inclusive economic growth and well-being. The implementation of the blue economy also encompasses the inland fisheries sector in line with the Ministry of Marine Affairs and Fisheries (KKP) program. Although South Sulawesi has the highest blue economy index, poverty in the province has increased in 2023. This study aims to analyze the relationship between fishery entrepreneurs, the Human Development Index (HDI), fishery production value, waste generation, extension services, fishery production volume, the distribution of GDP in the fishery sector, and the number of vessels with poverty rates using stepwise multiple linear regression. The results show that the number of fishery entrepreneurs positively affects poverty, while HDI and fishery production value significantly reduce poverty. Overall, improvements in HDI and production value are effective in reducing poverty, but the increase in the number of entrepreneurs has the opposite effect, as the majority of fishery businesses in South Sulawesi are still small-scale.